2022
DOI: 10.3390/futurepharmacol2010006
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look on Bergenin: Vision of Its Novel Drug Delivery Systems and Pharmacological Activities

Abstract: Bergenin (BER), a key constituent of Bergenia crassifolia (Saxifragaceae), has gained extensive attention, owing to its array of pharmacological actions, including anti-infective, anti-cancer, anti-diabetic, neuroprotective, hepatoprotective, anti-urolithiatic, anti-hyperuricemic, and anti-bradykinin properties. Despite ever-intensifying support for its therapeutic features, the poor solubility, lower oral bioavailability, shorter half-life, and more intestinal pH degradation (pH 6.8 or above) of BER have puzz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…In a recently published review article by Salimo et al [37], the antibacterial activity of bergenins was reported in 15 in vitro studies and 4 in vivo experiments [37]. Noteworthy, bergenin and its congeners participate in several mechanisms, such as lipid-peroxidation inhibitory activity and free-radical-scavenging activity [38], and initiate apoptosis and cell-cycle arrest in the G0/G1 phase [39]. Moreover, these compounds are able to easily cross the complex and multilayer lipopolysaccharide of bacteria cell walls, thereby causing lysis and cell death [40].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published review article by Salimo et al [37], the antibacterial activity of bergenins was reported in 15 in vitro studies and 4 in vivo experiments [37]. Noteworthy, bergenin and its congeners participate in several mechanisms, such as lipid-peroxidation inhibitory activity and free-radical-scavenging activity [38], and initiate apoptosis and cell-cycle arrest in the G0/G1 phase [39]. Moreover, these compounds are able to easily cross the complex and multilayer lipopolysaccharide of bacteria cell walls, thereby causing lysis and cell death [40].…”
Section: Discussionmentioning
confidence: 99%
“…Bergenin was examined in various anti-inflammatory models and was proven to be an efficient anti-inflammatory compound (Oliveira et al 2019). The compound has been thoroughly studied in terms of pharmacology and has emerged as a promising candidate for therapeutic uses (Mehta et al 2022). Due to the anti-inflammatory agents that were identified as chemical constituents of M. siamensis and M. repandus, as well as the abundant lupeol compound found in C. adansonii, there could be a reason to support the anti-inflammatory activity of the mixture of these three plants, which was the most potent in our observation.…”
Section: Determination Of Lupeol Content In Different Plant Extractsmentioning
confidence: 99%
“…Bergenin reportedly has anti-inflammatory, anti-anxiety, anti-malaria, anti-cancer, anti-diabetes, anti-hepatotoxicity, immunomodulatory, and neuroprotective pharmacological activities ( Rajesh et al., 2011 ; Liang et al., 2014 ; Gao et al., 2015 ; Jitender et al., 2017 ; Barai et al., 2019 ; Kumar et al., 2019 ; Shi et al., 2019 ; Xiang et al., 2020 ). Bergenin is widely distributed in higher plants and has been found in more than 90 plant species belonging to 37 genera in 20 families ( Mehta et al., 2022 ). The Chinese Pharmacopoeia lists the roots of Bergenia purpurascens and Ardisia japonica as natural bergenin resources for the medicinal extraction industry ( China Pharmacopoeia Committee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%